2013
DOI: 10.3109/08923973.2013.873048
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivoimmunomodulatory effect of all-trans-retinoic acid during Behçet’s disease: a study in Algerian patients

Abstract: Uveitis, recurrent oral and genital ulcerations associated with skin lesions are the major symptoms of a chronic multisystemic inflammatory disorder known as Behçet's disease (BD). High prevalence of this dreaded disease has been observed in the Mediterranean basin, including Algeria and along the Silk Road. Although the etiologic agent of this disease remains uncertain, many hypotheses have been advanced in its pathogenesis. Our team has previously reported high levels of nitric oxide (NO) in sera of BD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
3
4
0
Order By: Relevance
“…In our present study, ATRA significantly downmodulated in vitro NO production in AD patients. Our data are consistent with the findings reported by Rafa et al [48] and Djeraba et al [49] in inflammatory bowel diseases and Behçet disease, respectively. Similar results have been shown by many studies conducted on rat microglia [50,51].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our present study, ATRA significantly downmodulated in vitro NO production in AD patients. Our data are consistent with the findings reported by Rafa et al [48] and Djeraba et al [49] in inflammatory bowel diseases and Behçet disease, respectively. Similar results have been shown by many studies conducted on rat microglia [50,51].…”
Section: Discussionsupporting
confidence: 83%
“…Similar results have been shown by many studies conducted on rat microglia [50,51]. Consistent with several findings from other groups [49,52,53], our results suggest that ATRA can inhibit NO production in AD cells by regulating iNOS expression. Other research groups have reported a relationship between anti-inflammatory effects of retinoids and inhibition of the NF-κB and JAK/STAT signaling pathways [49,54,55].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Neither conventional treatments nor biologic diseasemodifying therapies can exert definite curative effects on RA. All-trans retinoic acid (ATRA) has received widespread attention as an active vitamin A derivative and an immune inflammation inhibitor (7), in addition to its ability to cure acute promyelocytic leukemia (APL) (8) and acne (9). With regard to the role of ATRA in immune inflammatory responses, ATRA reportedly participates in ameliorating inflammatory response in the epididymis by downregulating pro-inflammatory cytokines and upregulating anti-inflammatory factors (10).…”
mentioning
confidence: 99%
“…In a recent study, our team showed the over-expression of NF-B in Behçet patients PBMCs. Increased NF-B expression is concomitant with the overexpression of iNOS, the enzyme that produce NO [39]. In the same way, Hamzaoui et al reported increased IL-18 expression when they stimulated patients cells cultures (from broncho-alveolar lavage fluid) with LPS [25].…”
Section: Discussionmentioning
confidence: 94%